(untitled) (Світ фінансів, 2017)
Ляшенко О. М., Булавська Г. О. Модель бюджету витрат на комерціалізацію інновацій. Висвітлено проблеми управління фінансуванням комерціалізації інновацій, і зокрема, проблему формування бюджету комерціалізації. Розроблено модель планування витрат на комерціалізацію винаходу при різних способах фінансування бюджету комерціалізації та з врахуванням бюджетних обмежень, що зумовлюють змінний характер розподілу витрат. Lyashenko O., Bulavska H. The model of expenditures budget on innovation commercialization. One of the problems of financial management in innovation commercialization – the budget process of commercialization – is investigated in the article. The authors have elaborated the model of expenditures planning for invention commercialization due to the different ways of commercialization budget financing and under budget restrictions’ procedure which assumes the variability of expenditures to be distributed.